THE ARGUMENT-DRIVEN INQUIRY TRAINING FOR SCIENCE TEACHERS IN PALANGKA RAYA CITY - Ruli Meiliawati; Suandi Sidauruk; AT Siahaan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
Integrating laboratory activities with learning activities is a separate dynamic for science teachers, because learning science (Chemistry, Physics, and Biology) will be "bland" because students do not get valuable practical experience. Argument-Driven Inquiry (ADI) is a learning model in which teachers can change conventional laboratory learning into integrated laboratory learning. This learning combines laboratory activities with other learning activities such as reading, lectures, and discussions. The purpose of this service is to introduce and train teachers in designing ADI-based learning. The Service Method is carried out in three stages, namely: 1) Preparatory Stage; 2) Implementation Stage; and 3) Evaluation Stage. The results achieved after participating in this workshop were being able to design learning based on the ADI Model. In addition, this activity received a positive response (78%) towards the development of science learning activities at the senior high school level